Efektivitas Penggunaan Media Balok Cuisenaire dalam Pembelajaran Matematika Kelas I SD Muhammadiyah 1 Gondrong Kota Tangerang - Cahyani, Astria Indah; Nurhayati, Siti; Awiria, Awiria (MASALIQ, 2021)
This study aims to determine whether or not the use of Cuisenaire block media is effective in calculating students' mathematics sums. This study uses a quasi-experimental research method with the Noneequivalent Control Group Design. The population subjects in this study were students of class I SD Muhammadiyah 1 Gondrong Tangerang City by taking a sample of two classes of 42 students, namely class I A totaling 20 students as the control class. The data collection technique used the instrument of concept understanding test in the form of an essay consisting of 10 valid and reliable questions. To test the pretest hypothesis, calculate manually, in this study the t-test was used. The t-test results obtained a value of 3.97 > 2.093, which means that there is a significant difference in the learning outcomes of Mathematics using Cuisenaire blocks and those without Cuisenaire blocks. while for testing the experimental class hypothesis 1.141 < 2.080, it means that there is no difference in the understanding of mathematical arithmetic in addition to the results of the pretest and posttest data. This means that the learning outcomes of Mathematics using Cuisenaire blocks are higher than those without Cuisenaire blocks.